Beyond Biological Sex: Interactive Effects of Gender Role and Sex Hormones on Spatial Abilities - Pletzer, Belinda; Steinbeisser, Julia; van Laak, Lara; Harris, TiAnni (Frontiers in Neuroscience, 2019)
Sex differences in spatial abilities are well documented, even though their underlying causes are poorly understood. Some studies assume a biological basis of these differences and study the relationship of sex hormone levels to spatial abilities. Other studies assume social influences and study the relationship of gender role (masculinity/femininity) to spatial abilities. Contemporary theories postulate a psychobiosocial model of sex differences in spatial abilities, in which both biological (e.g. hormonal) and psychosocial (e.g. gender role) variables interactively modulate spatial abilities. However, few studies have addressed both aspects simultaneously. Accordingly, the present study explores potential interactive effects between gender role and sex hormones on spatial performance. 41 men and 41 women completed a mental rotation and a virtual navigation task. Sex hormone levels and gender role were assessed in all participants. Sex differences favouring men were observed in both tasks. We found that neither sex hormones nor gender role alone emerged as mediators of these sex differences. However, several interactive effects between gender role and sex hormones were identified. Combined effects of masculinity and testosterone were observed for those variables that displayed sex differences. Participants with both, high masculinity and high testosterone showed the best performance. However, this association was further modulated by biological sex and progesterone levels. Furthermore, we observed an interactive effect of femininity, estradiol and testosterone on response times in both tasks. Consistent across both tasks and irrespective of biological sex, testosterone related to response times in participants with low estradiol levels, depending on their femininity. In participants with low femininity, testosterone was related to slower reaction times, while in participants with higher femininity, testosterone was related to faster reaction times. (273 words)